Angong Niuhuang Wan ameliorates LPS-induced cerebrovascular edema by inhibiting blood‒brain barrier leakage and promoting the membrane expression of AQP4 - Liu, Bo-Tong; Li, Quan; Sun, Kai; Pan, Chun-Shui; Huo, Xin-Mei; Huang, Ping; Yan, Li; He, Qi-Hua; Zhong, Li-Jun; Wang, Yuan; Hu, Meng-Lei; Li, An-Qing; et al. (Frontiers in Pharmacology, 2024)
Introduction Angong Niuhuang Wan (AGNHW), developed during the Qing dynasty (18th century) for the treatment of consciousness disturbances caused by severe infections, has been used to treat brain edema caused by ischemia‒reperfusion. However, it remains unclear whether AGNHW can ameliorate vascular-origin brain edema caused by lipopolysaccharides (LPS). This study explored the ameliorative effects of AGNHW on LPS-induced cerebrovascular edema in mice, as well as the potential underlying mechanisms. Methods A cerebrovascular edema model was established in male C57BL/6N mice by two intraperitoneal injections of LPS (15 mg/kg), at 0 and 24 h. AGNHW was administered by gavage at doses of 0.2275 g/kg, 0.455 g/kg, and 0.91 g/kg, 2 h after LPS administration. In control mice, normal saline (NS) or AGNHW (0.455 g/kg) was administered by gavage 2 h after intraperitoneal injection of NS. The survival rate, cerebral water content, cerebral venous FITC-dextran leakage, Evans blue extravasation, and expression of vascular endothelial cadherin (VE-cadherin), zonula occludens-1 (ZO-1), claudin-5, phosphorylated caveolin-1 (CAV-1), and cytomembrane and cytoplasmic aquaporin 1 (AQP1) and aquaporin 4 (AQP4) were evaluated. The cerebral tissue phosphoproteome, blood levels of AGNHW metabolites, and the relationships between these blood metabolites and differentially phosphorylated proteins were analyzed. Results AGNHW inhibited the LPS-induced decrease in survival rate, increase in cerebral water content, decrease in VE-Cadherin expression and increase in phosphorylated CAV-1 (P-CAV-1). AGNHW treatment increased the expression of AQP4 on astrocyte membrane after LPS injection. AGNHW also inhibited the LPS-induced increases in the phosphorylation of 21 proteins, including protein kinase C-α (PKC-α) and mitogen-activated protein kinase 1 (MAPK1), in the cerebral tissue. Eleven AGNHW metabolites were detected in the blood. These metabolites might exert therapeutic effects by regulating PKC-α and MAPK1. Conclusion AGNHW can ameliorate cerebrovascular edema caused by LPS. This effect is associated with the inhibition of VE-Cadherin reduction and CAV-1 phosphorylation, as well as the upregulation of AQP4 expression on the astrocyte membrane, following LPS injection.